Heavy Metals in Surface Soils of Kota Bharu Landfill Site and its Relations to The Growth and Macronutrients Uptake of Acacia Mangium - Nik Jaafar, Nik Mohd Shibli (2003)
A study of heavy metals distribution in landfill surface soil, surface water and landfill leachate and its relations to Acacia mangium growth and macronutrients uptake was conducted in a landfill in Kota Bharu, Kelantan. Five heavy metals, particularly Fe, Cr, Zn, Cu and Cd was analyzed in this study and results shows elevated heavy metals concentration level compared to the control surface soil. The distribution of the heavy metals in the surface soil from the landfill varies throughout the study site. The concentration decreased prominently in the river sediment adjacent to the landfill. The concentration of Fe was the highest that ranged between 1993.4 – 2404.6μg/g, followed by Zn, 18.08 – 54.10 μg/g; Cr, 2.67 – 62.10 μg/g; Cu, 5.21 – 18.60 μg/g and Cd, 0.70 – 1.52 μg/g of soil dry weight. However, compared to DOE soil threshold concentration, this landfill was only slightly contaminated with Cd that exceeds the threshold with an average of 0.94 μg/g. Heavy metals speciation by sequential extraction of landfill surface ii soil shows that the surface soil was not yet contaminated with heavy metals as the anthropogenic fraction is less than 30% of the total concentration of heavy metals of the surface soil and mainly attached to the organic matter. Concentration of heavy metals in landfill leachate shows higher level than the surface water. However, the levels of heavy metals in both water samples were still considered as low compared to other landfills due to dilution by rain and river nearby. Cu concentrations in water samples were generally higher than other heavy metals that ranged between 0.03 – 6.14 mg/L whereas Cd and Cr were generally very low, below detectable limits. The level of accumulation in A. mangium leaves was highest for Fe that ranged between 139.5 – 537.6 μg/g, followed by Cr 45.54 – 357.3 μg/g, Zn 29.36 - 57.23μg/g, Cu 6.88 - 15.61μg/g and Cd 1.63 - 3.48μg/g. However, Fe shows no significant difference in the level of accumulation between landfill and control plants. Heavy metals accumulation level in A. mangium leaves have very wide range dependent on the leaves sampled. However, from the soil-plant concentration ratio, heavy metals uptakes by A. mangium in landfill site were found higher than control plants especially for Cr and Cd. Generally the concentration of heavy metals was found so much higher in the plants tissues rather than in the landfill surface soil and landfill leachate or surface water. Relation between heavy metals accumulation in A. mangium and growth and macronutrient uptake was not demonstrated this study as the N, P, K level in control and landfill site do not show any significant correlation with heavy metals concentrations. Uptakes of N and P in landfill A. mangium were found higher than control but on the contrary, K was found higher iii in control plants. Growth of A.mangium in landfill was slightly different with control plants as there are tendency of A. mangium in landfill site to produce many branches, leaves and incisive increase of trunk diameter whereas, control plants tends to gained heights very quick. This is due to different soil type and climatic factors influence rather than heavy metals level in the plants’ tissue. This study also proposed A. mangium is tolerant to Cd and Cr however the use of A. mangium as general bioindicator for heavy metals was not probable as only Cd and Cr was highly accumulated. A. mangium can be used for phytoremediation of low contaminated soil as shown in his study. Furthermore, landfill site is this study found it suitable to be used as A. mangium culture site.